(untitled) (Journal of the College of Basic Education, 2022)
The study came under the title Aesthetics of Taboos and Interviews in the book (The Fall of the Zind) by Abu Al-Alaa Al-Maari, to shed light on the aesthetics of these two arts in his poetry, and how the poet benefited from them in drawing images and rhetorical scenes affecting the recipient, as the study relied on presenting a rhetorical lesson based on explanation, analysis and perception. The aesthetic elements in all its dimensions, and the study was divided into two chapters, the first concerned with the beauty of the counterpoint, both positive and negative, and the second was concerned with the aesthetics of the interview and the two chapters were preceded and followed by the most important results, then proven by sources and references.